Microbiota Disease - Álvaro Zamudio-Tiburcio; Héctor Bermúdez-Ruiz; Pedro Antonio Reyes-López (Open Journal of Bacteriology - Peertechz Publications, 2019)
The authors try to describe the Microbiota Diseases, like a process thatbrings together a number of conditions, caused by dysbiosis and that occur fudamentally in the devices and systems: Immunological, Gastrointestinal, Dermatological, Psychiatric, Neurological, Endocrinological and others. In order to draw attention to the need to strengthen ties of union between all those interested in the subject, to shorten resources, times and establish development criteria, this review is published. Without a doubt, it will make this Diseases, accepted, can be strengthened and direct talents for the benefi t of the millions of human beings affected by this problem.